Composite Materials Obtained via Two-Nozzle Electrospinning from Polycarbonate and Vinylidene Fluoride/Tetrafluoroethylene Copolymer; Inorganic Materials: Applied Research; Vol. 9, iss. 2 - Bolbasov E. N. Evgeny Nikolaevich; Buznik V. M. Vyacheslav Mikhaylovich; Stankevich K. S. Ksenia Sergeevna; Goreninsky S. I. Semen Igorevich; Ivanov Y. N. Yuriy Nikolaevich; Kondrasenko A. A. Aleksandr Aleksandrovich; Gryaznov V. I. Vladimir Ivanovich; Matsulevich A. N. Andrey Nikolaevich; Tverdokhlebov S. I. Sergei Ivanovich (2018, 2018)
Title screen